The Influence of Sustainable Development Module on the Values and Beliefs of First-Year Students in Undergraduate Engineering Education - Amashi, Radhika; Joshi, Gopalkrishna; Kandakatla, Rohit (Journal of Engineering Education Transformations, 2021)
Education for Sustainable Development (SD) has become vital in the field of engineering education because there is a need that engineers of the 21st century should not only build technologies and solutions that meet human needs but are also expected to situate their professional practice in the context of society and the environment. Currently, most of the literature right now is focused on integrating the concept of SD in engineering education either at the first or higher semesters of the undergraduate program. To our knowledge, these studies discuss the process of integration, the impact of integration on student learning outcomes, desired competencies for SD, different teaching and learning strategies, and understanding student perception about SD. However, this study contributes to the literature by examining how this integration is influencing student`s knowledge, values, and behaviors in the first year of engineering as the outcome of integration. In this paper, we examine one such effort and try to investigate the impact of an SD module that was introduced to first-year engineering students as part of an engineering exploration course. Embedded mixed methods were used to understand the impact of introducing the SD module on student`s knowledge, beliefs, and values. From the results, we observe that there was no significant change in knowledge when analyzed quantitatively however qualitative analysis showed that the module had influenced students to transition from basic awareness about SD to accepting or committing to SD principles and finally reporting to take actions towards sustainable living and development.